Insulin resistance and obesity affect monocyte-derived dendritic cell phenotype and function. (December 2020) - Paccosi, Sara; Pala, Laura; Cresci, Barbara; Silvano, Angela; Cecchi, Marta; Caporale, Roberto; Maria Rotella, Carlo; Parenti, Astrid
Highlights: Obesity and insulin resistance role on dendritic cells (DC) function was investigated. DC from T2DM obese post-menopausal woman express higher mRNA of integrins. Dendritic cells from T2DM obese post-menopausal woman were dysfunctional. Fetuin and adiponectin in T2DM obese post-menopausal woman were negatively correlated. Hyperglycaemia significantly impaired CD14 + trans-differentiation into DC. Abstract: Aim: Cardiovascular disease (CVD) is prevalent in women after menopause, which may be associated with obesity, insulin resistance and metaflammation. Despite the recognized role of immunological mechanisms in vascular remodeling, the role of dendritic cells (DCs) is still unclear. The aim was to characterize monocyte-derived DCs (Mo-DC) in post-menopausal patients with type 2 diabetes (T2DM) and obese woman, without clinical manifestations of atherosclerosis. Methods: Obese post-menopausal women with or without T2DM were enrolled and were compared to age-matched healthy women. DCs obtained from patients were phenotypically and functionally characterized by flow cytometry and mixed lymphocyte reaction. MRNA integrins expression was assessed by real time RT-PCR; circulating fetuin-A and adiponectin levels were measured by ELISA. Results: Phenotypic dysregulation of Mo-DC reported was related to a defective allogenic lymphocyte stimulation and to an increased mRNA of CD11c, CD18 and DC-SIGN/CD209 which regulate their adhesion to vascular wall cells. Fetuin-A and adiponectin levels were significantly altered and negatively correlated. Hyperglycaemia significantly impaired CD14 + transdifferentiation into Mo-DC. Conclusions: These data show a dysfunction of Mo-DCs obtained from precursors isolated from T2DM obese post-menopausal woman without any documented clinical CV event. Association of obesity to diabetes seems to worsen DC's phenotype and function and increase vascular inflammation.